IDENTIFICATION OF RIFAMPICILIN-RESISTANT MYCOBACTERIUM TUBERCULOSIS STRAINS BY POINT MUTATION ANALYSIS OF RPOB GENE - Minh, Nghiêm Ngọc (Vietnam Journal of Biotechnology, 2011)
Mycobacterium tuberculosis (MTB) is a pathogenic baterial    species   in   the   genus   of   Mycobacterium causing most cases of tuberculosis. As reported  by WHO tuberculosis threatens the health of one third of the world's population.    The   most   facing   problem     which    makes   tuberculosis     become     more    seriously   is   the appearance   of  antibiotic-resistant   TB   strains  classified     as  Multi-drug   Resistant   TB   (MDR-TB),   Extensively Drug   Resistant   (XDR)   and   TB   co-infected      with   HIV/AIDS.   Screening   and   detection       drug-resistant   strains would   help the treatment   and  diagnosis  for  tuberculosis   more effective   in  patients. Advantages  in molecular biological techniques such as PCR, real-time PCR allow researchers rapidly, exactly identity the drug-resistant M.tuberculosis   strains  isolated from   patients. In this study, primer pairs rpoB-F  and rpoB-R were designed to  amplify    the   rifampicin   resistance   determining  region   (RRDR)   including   27   codon   of  the   rpoB gene.   After  amplified   sequences  of Mycobacterium   tuberculosis strains isolated   from   7 patients  of the central  hospital in Hue,  the   were forwarded for   sequencing.  The   Results  of  sequence   analysis   showed   that   a mutation   at the  codon 531 detected. And this result was useful   method to change the treatment for these patients.